The Contribution of Liquidity and Profitability to Firm Value with Capital Structure as a Mediating Variable - Alif Syawandary; Dicky Jhoansyah; Tetty Sufianty (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Fluctuating economic conditions have increased challenges in maintaining manufacturing firms’ value. This study aims to analyze the effect of liquidity and profitability on firm value, with capital structure as a mediating variable, among manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2023. The approach used is quantitative associative with the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. The research sample was selected using a purposive sampling technique, resulting in 147 manufacturing companies. The variables used include liquidity (Current Ratio/CR), profitability (Return on Assets/ROA), capital structure (Debt to Equity Ratio/DER), and firm value (Price to Book Value/PBV). The results of the study indicate that, liquidity has no significant effect on firm value, profitability has a positive and significant effect on firm value, capital structure has a positive and significant effect on firm value, capital structure can mediate the effect of liquidity on firm value (full mediation) and capital structure can mediate the effect of profitability on firm value (partial mediation). These findings indicate that increasing profitability and optimal capital structure management are key factors in increasing the value of manufacturing companies in Indonesia.